Efek Ekstrak Bunga Kecombrang (Etlingera elatior) sebagai Repellent Nyamuk Aedes aegypti - Zulfikar Zulfikar; Mahdinursyah Mahdinursyah; Wiwit Aditama (Poltekkes Kemenkes Yogyakarta, 2017)
One way to protect ourselves from the bite of Aedes aegypti is by using repellent. Some repel-lents show toxic effects, including those that contain diethyltoluamide (DEET) as the active ingre-dient. This study aimed to determine the effect of Kecombrang flower (Etlingera elatior) extract as a repellent against Aedes aegypti mosquito. This study was carried out experimentally with 5 treatment groups. The mean of rejection time of the observation on the repellent effect of 25 %, 50 %, and 100 % Kecombrang flower extract concentrations on Ae. aegypti mosquito, were 5,4 minutes, 8,4 minutes, and 13 minutes, correspondingly. In the control group, the mosquitoes have bitten since the first minute of the observation, whereas in the 15 % DEET group, the mos-quitoes did not bite until the end of the 120 minutes observation. The one way Anova test results showed that there was a significant difference between the treatment groups (p<0,001). Among the extract groups also showed significant differences, except between the 25 % extract group and 50 % extract group. The observation results on the group of 100 % extract showed less number of Ae. aegypti mosquitoes bites compared to 25 % and 50 % extract concentration groups. So, the greater the dose of Kecombrang flower extract, the greater the effect of repellent produced as well as the number of mosquito bites which showed an increase with increasing observation time. Kecombrang flower extract had repellent effect against Ae. aegypti mosqui-toes, but it was far below the 15 % DEET effect. The group of 100 % Kecombrang flower extract concentration showed longer repellent effect compared to the groups contain of 25 % and 50 % extracts.